Sympathoneural and Adrenomedullary Responses to Mental Stress. Issue 1 (23rd December 2014) - Carter, Jason R.; Goldstein, David S.
Abstract: This concept‐based review provides historical perspectives and updates about sympathetic noradrenergic and sympathetic adrenergic responses to mental stress. The topic of this review has incited perennial debate, because of disagreements over definitions, controversial inferences, and limited availability of relevant measurement tools. The discussion begins appropriately with Cannon's "homeostasis" and his pioneering work in the area. This is followed by mental stress as a scientific idea and the relatively new notions of allostasis and allostatic load. Experimental models of mental stress in rodents and humans are discussed, with particular attention to ethical constraints in humans. Sections follow on sympathoneural responses to mental stress, reactivity of catecholamine systems, clinical pathophysiologic states, and the cardiovascular reactivity hypothesis. Future advancement of the field will require integrative approaches and coordinated efforts between physiologists and psychologists on this interdisciplinary topic. Published 2015. Compr Physiol 5:119‐146, 2015.